The Impact of Nutrition, Helminth Infection, and Lifestyle on Elementary School Student’s Achievement - Buntoro, Ika Febianti; Deo, Dwita Anastasia; Woda, Rahel Rara (Journal of Tropical Life Science, 2017)
There is a lot of helminth infections and malnutrition cases in Indonesia. Some of the effects of helminth infection are anemia, diarrhea, malnutrition, intestinal obstruction, growth and developmental disorder, and also cognitive impairment. This study aimed to explore the impact of nutrition, helminth infection, and lifestyle on elementary school students’ achievement. An observational analytical study with the cross-sectional design was used. The study was participated by 65 elementary school students grade 3, 4, and 5. The study was conducted in Pasir Panjang Elementary School, Kupang, Nusa Tenggara Timur, Indonesia. The data was analyzed using chi-square. There were 7 students (10.77%) having helminth infections:4 students (57.1%) had Ascarislumbricoides infection, 2 students (28.6%) had Enterobius vermicularis infection, and 1 student (14.3%) had Strongyloides stercoralis infection. There were no differences found on students’ achievement between students with normal and low nutritional state (p = 0.917; p > 0.05) and between different lifestyle habit (p = 0.768; p > 0.05). However, a significant difference in students’ achievement was found between students with and without helminth infection (p = 0.036; p < 0.05). Helminth infection had a significant impact on elementary school students’ achievement, but no significant impact found for differences in nutritional state and lifestyle habit.